Sunitinib induces PTEN expression and inhibits PDGFR signaling and migration of medulloblastoma cells - Castellino, R.C. (2011)
We previously showed that inhibition of the platelet-derived growth factor receptor (PDGFR) blocks the survival and migration of medulloblastoma cells. Identification of in vitro PDGFR-targeting pharmacologic agents that are suitable for preclinical testing in medulloblastoma models in vivo will be critical for efficiently translating these agents to clinical investigation in children with medulloblastoma. In this study, we investigated whether the multi-tyrosine kinase inhibitor sunitinib, effectively inhibits PDGFR signaling required for medulloblastoma cell migration. Daoy and D556 human medulloblastoma cells pre-treated for 1 h with 0.2 μM sunitinib demonstrated induction of PTEN expression and significant inhibition of PDGFR signaling activity and transactivation of EGFR, in a RAS-independent manner, in response to PDGF-BB stimulation. Sunitinib pre-treatment markedly reduced medulloblastoma cell migration in response to both PDGF-BB and 10% serum at 4 and 24 h after treatment. Pre-treatment with sunitinib for 1 h also resulted in detachment and decreased viability of D556, but not Daoy, cells and only after 48 h following treatment. However, sunitinib did not induce apoptosis in either cell line at any time point, indicating that the anti-migratory effects of sunitinib were not due to impeding cell survival. Sunitinib similarly inhibited PDGFR signaling and migration of primary murine Smo/Smo medulloblastoma cells, suggesting that the Smo/Smo mouse is an appropriate model for preclinical testing of sunitinib. These results indicate that sunitinib may be an important pharmacologic agent for the treatment of invasive medulloblastoma, particularly given evidence of its ability to cross the blood–brain barrier to target tumor cells, and thus warrants further in vivo testing for confirmation of efficacy.